2012
DOI: 10.1371/journal.pone.0041375
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying Controlling Nodes in Neuronal Networks in Different Scales

Abstract: Recent studies have detected hubs in neuronal networks using degree, betweenness centrality, motif and synchronization and revealed the importance of hubs in their structural and functional roles. In addition, the analysis of complex networks in different scales are widely used in physics community. This can provide detailed insights into the intrinsic properties of networks. In this study, we focus on the identification of controlling regions in cortical networks of cats’ brain in microscopic, mesoscopic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 56 publications
1
63
0
Order By: Relevance
“…It is also shown that the minimum number of driver nodes is determined mainly by the degree distribution of the network. Many other studies of controllability in complex networks have followed, including [20], [19], [23], [24], [21].One issue with the approach taken by [16] and much of the follow up work is that the quantitative notion of controllability discussed in [16] (namely, the number/fraction of required driver nodes) is rather crude in some settings. This was noted, for example, by [18] in response to the surprising result in [16] that genetic regulatory networks seem to require many…”
mentioning
confidence: 99%
“…It is also shown that the minimum number of driver nodes is determined mainly by the degree distribution of the network. Many other studies of controllability in complex networks have followed, including [20], [19], [23], [24], [21].One issue with the approach taken by [16] and much of the follow up work is that the quantitative notion of controllability discussed in [16] (namely, the number/fraction of required driver nodes) is rather crude in some settings. This was noted, for example, by [18] in response to the surprising result in [16] that genetic regulatory networks seem to require many…”
mentioning
confidence: 99%
“…Studying the effects of mixed time-delayed coupling on other collective behaviors of coupled nonlinear oscillators is certainly an interesting subject for future investigations. Finally, our findings in this work should attract general interest from researchers in the fields of nonlinear dynamics and have great potential for applications in systems biology, ecology, signal processing, and neuroscience [66].…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…Although (Tang et al, 2012a) investigated the controllability problem of complex networks, unfortunately, the network considered is undirected. Therefore, Tang, Gao, Zou, and Kurths (2012b) concentrates on the identification of controlling regions in neuronal networks of cats' brain, based on singleobjective evolutionary computation methods, in which the network is directed. Then, one simple way to treat the controllability of directed networks is to consider the two measures of controllability P and r, separately.…”
Section: Local Controllabilitymentioning
confidence: 99%
“…Evidently, the way regarding the objectives P and r separately is unavoidable to induce conservativeness (Tang et al, 2012b).…”
Section: Local Controllabilitymentioning
confidence: 99%